The Effect of Anthelmintics in the Fight Against Cysticercosis in Sheep - o‘g‘li, Alikulov Zohid Inadulla; Mirabosovich, Aminjonov Sherzod (American Journal of Botany and Bioengineering, 2024)
This article provides a brief overview of the causes, biology, and effectiveness of anthelmintic drugs in combating cestodosis of sheep (Cysticercus tenuicollis).